Architectenwoningen in het Brussels Hoofdstedelijk Gewest (1830-1970) - Stephanie Van de Voorde; Linsy Raaffels; Barbara Van der Wee; Inge Bertels (Brussels Studies, 2024)
Architects’ houses constitute a unique category of housing, embodying a special significance as a calling card, an experimental endeavour, a culmination, or a synthesis of the architect’s body of work, encompassing stylistic, geographical, technical, social, and other features. However, to comprehensively grasp the significance and added value of this architectural genre, a well-defined theoretical and typological framework for understanding architects’ houses is essential. Based on data gathered from existing inventories, literature, archival research and on-site visits, an extensive register in which 370 architects’ houses in the Brussels-Capital Region were mapped forms the starting point of the analysis. Focusing on the period 1830-1970 in which the construction of both architects’ houses and housing in general was increasing, this register includes iconic and well-known architects’ houses as well as less studied cases, in approximately equal proportion: many of which were previously unidentified and can now be properly identified as architects’ houses. Representing the diversity of these houses, the register forms the necessary basis for a thorough assessment of individual cases as well as the architect’s house as a distinct building type.